The possibility of manufacturing a biocidal of Bacillus spp. and their growth on different fermented media - Ali Salman Abbas; Wissam Adnan R. Aljuaifari (Kufa Journal for Agricultural Sciences)
The study was conducted in the Molecular Biology Laboratory - Department of Plant Protection - Faculty of Agriculture - University of Kufa during 2020-2021 to evaluate the possibility of producing a biocide from Bacillus spp. B. firmus, B. cereus. and B. simplex. The results of manufacturing bionematicide from these bacteria showed that the three species did not differ in their growth on the same compost medium (palm fronds, rice residues, wheat residues), while the growth of each Bacillus spp. differed from other species on different culture media. The palm frond medium, regardless of the type of bacteria, was the least favorable and did not support many bacterial populations, and allowed no more than 83*108 CFU. Whereas the bacterial colonies ranged from 219*108 CFU to 254*108 CFU on fermented wheat residues, with a slight difference from rice residues, which led to bacterial colonies of 198*108 CFU to 214*108 CFU. In the case of carriers used for the biocide, preparation using sand was always better than with calcium sulfate. The effect of packing materials (plastic bags, paper bags, or plastic containers) on the efficiency and vitality of bacteria in the biocide content was also evaluated. It is noted that the highest bacterial colonies, which ranged from 267 to 253 *108 CFU, in the case of using plastic containers significantly differed from storing in paper bags (233-230*108 CFU) and plastic bags (235 -216 *108 CFU), after 15 days of storage in laboratory conditions. However, the viability and effectiveness of the prepared biocide decreased with the increase of storage periods to 30, 60, and 90 days, regardless of the type of bacteria.